Prevalence of dental caries, periodontal disease, malocclusion, and tooth wear in indigenous populations in Brazil: a systematic review and meta-analysis - Janete Maria REBELO VIEIRA; Juliana Vianna PEREIRA; Emílio Carlos SPONCHIADO JÚNIOR; Alana Cristina Caldeira CORRÊA; Ana Beatriz Santos dos SANTOS; Thaís Soares da SILVA; Walbert de Andrade VIEIRA; Larissa Neves QUADROS; Maria Augusta Bessa REBELO (Brazilian Oral Research, 2023)
Abstract The aim of this review was to evaluate the prevalence of dental caries, periodontal disease, malocclusion, and tooth wear in indigenous in Brazil. A systematic review of observational studies was performed according to the PRISMA guidelines (CRD42020218704). The search strategy involved the electronic databases of Embase, LILACS, PubMed, Web of Science, Scopus, and the CAPES Theses and Dissertations for gray literature. The eligibility criteria consisted of publications that assessed the prevalence of oral conditions in indigenous populations in Brazil. Studies with indigenous people living in urban area were excluded. The risk of bias was evaluated by using JBI Critical Appraisal for prevalence studies. Thirty studies were included in the review, and the majority showed a low risk of bias. A meta-analysis of 20 studies was conducted using the random-effects model and a 95% confidence interval. Several ethnicities were studied in isolation or in groups (n = 7,627 for dental caries; n = 2,774 for periodontal disease; n = 1,067 for malocclusion; n = 150 for tooth wear). The prevalence of caries ranged from 50% among indigenous people aged 18-36 months to 100% among those aged 65–74 years. The prevalence of periodontal disease ranged from 58% to 83%. The prevalence of malocclusion was 43%. Tooth wear was assessed in only one ethnic group and showed a prevalence of 100% in indigenous people aged >18 years. The certainty of evidence assessed by the GRADE system ranged from very low to moderate. This systematic review showed significant differences in the prevalence of dental caries, periodontal disease and malocclusion between indigenous population groups and territories in which indigenous people live.